Trichosanthes dioica Roxb.: A vegetable with diverse pharmacological properties - Mahia Khandaker; Saleha Akter; Mohammad Zafar Imam (Food Science and Human Wellness)
Trichosanthes dioica Roxb. is a climber of the Cucurbitaceae family mainly found in tropical Asia. The fruit is widely consumed as a vegetable and different parts of this plant are used in the traditional medicine to treat various types of human ailments. In this review, we critically analyzed and presented the scientific studies on T. dioica available in three electronic databases viz. PubMed, Web of Science and Google Scholar. Our aim was to find the scientific basis of the traditional use to understand the plant’s potential in therapy. Studies have found promising antihyperglycemic, antihyperlipidemic, antitumor, cytotoxic, arsenic poisoning ameliorative, anti-inflammatory, antidiarrheal, and varieties of pharmacological activities of T. dioica. Different types of bioactive compounds have been identified and isolated from T. dioica including peptides namely trichosanthin and lectin; a number of triterpenes like cucurbitacin B, euphol, α-amyrin, β-amyrin, lupeol, taraxerol, betulin, and karounidiol; sterols, steroidal saponin, tannin, flavonoids etc. T. dioica contains a number of well-known bioactive phytochemicals and the plant has shown an array of pharmacological activities in vivo. This review will expand our understanding of the therapeutic potential of T. dioica and their phytochemical basis which may help in further research on this species. Keywords: Trichosanthes dioica, Pointed gourd, Cucurbitaceae, Ethnomedicine, Ethnopharmacology